Enhancing first aid knowledge for students at SDN Mojorejo 2 Sragen - Irma Mustika Sari; Erika Dewi Noorratri (Universitas Muhammadiyah Magelang, 2024)
Elementary education is a time when children actively interact with their friends. Play interactions sometimes carry a risk of injury for elementary school children. The national incidence of injuries at school is 5.4%. The highest prevalence rate of injury occurs in school children, namely 13%, and in the age range of 5-14 years. Inappropriate first aid can have detrimental effects on the victim. The aim of this community service activity is to increase students' knowledge of first aid for minor injuries. The method of implementing the service is through counseling using video media and training in treating minor injuries. After providing counseling and training on treating minor injuries to students at SDN Mojorejo II Sragen, they showed an increase in